PENGARUH MEDIA AMPLOP MISTERIUS TERHADAP MOTIVASI DAN HASIL BELAJAR IPS SISWA MTs NEGERI 2 PROBOLINGGO - Kulsum, Umi; Feri Ferdiyanto (Universitas Islam Zainul Hasan Genggong, 2023)
Low student learning outcomes can come from students, teachers, low motivation, inadequate facilities and infrastructure, students being less active in the learning process, and a lack of variety in learning methods and learning media used by teachers. The aim of this research is to determine the effect of mysterious envelope learning media on student motivation and learning outcomes in social studies subjects. This research uses a preexperimental design with one group preset-posttest. The sample for this research was class VIII E students at MTs Negeri 2 Probolinggo, totaling 20 students. Data analysis used SPSS 22, namely descriptive analysis, normality test, homogeneity test, paired/dependent t test. The research results obtained from questionnaire data and pretest and posttest scores for class VIII E MTs Negeri 2 Probolinggo students show that there are differences in learning motivation and student learning outcomes between before receiving treatment and after receiving treatment. Because the student learning motivation data has a value of t=52.838> 2.02269, thus H0 is rejected and Hi1 is accepted. And in the pretest-posttest value, the value of t = 23.006 > 2.02269, thus H0 is rejected and Hi2 is accepted. So it can be concluded that there is an influence of the mysterious envelope learning media on students' motivation and social studies learning outcomes.